A Lung Model to Demonstrate Dynamic Gas Trapping and Intrinsic Positive End-Expiratory Pressure at Realistic Ventilation Settings. Issue 6 (November 2017) - Freebairn, S. H.; Imlay, R.; Barrett, E.; Park, M. A. J.; Freebairn, R. C.
Intrinsic positive end-expiratory pressure (PEEP) and gas trapping are recognised hazards during ventilation of patients with airflow obstruction. Demonstration of these phenomena on conventional lung models using realistic ventilation settings is difficult. We describe an Intrinsic PEEP Model that is able to demonstrate dynamic gas trapping and intrinsic PEEP at realistic ventilation settings, and demonstrate its ability to develop intrinsic PEEP in a timeframe useful for teaching. The model uses a Heimlich valve to permit a lower resistance on inspiration than expiration. The model was tested using a series of typical ventilation settings which, when applied in a clinical setting on patients with airflow obstruction issues, would result in prolonged low expiratory flow and the development of intrinsic PEEP of 10 to 20 cmH2 O, and ultimately significant gas trapping. The IPM can be used to demonstrate this effect and the ventilator adjustments required to minimise these problems.